Lelutung Tokak (Tabernaemontana macrocarpa Jack.) sebagai Sumber Zat Bioaktif Antioksidan dan Antikanker - DJIHAN RYN PRATIWI; MARIA BINTANG; PARTOMUAN SIMANJUNTAK (Fakultas Farmasi Universitas Pancasila, 2014)
This research was aimed to determine biologic activities of n-hexane, ethylacetate, ethanol and water extracts of lelutung tokak (Tabernaemontana macrocarpa Jack.) stem as antioxidant and anticancer. The result of this research showed that four extracts of T. Macrocarpa Jack. stem have antioxidation and anticancer activity. The antioxidant activity test with brine shrimp lethality test (BSLT) showed the LC50 value of n-hexane, ethylacetate, ethanol and water extracts of lelutung tokak stem were 567.89; 119.34; 120.56 and 156.44 ppm respectively; with DPPH method were 653.54; 48.10; 53.322 and 121.02 ppm, respectively. The anticancer test result showed that the IC50 of ethylacetate and ethanol extracts were 6.04 and 7.14 ppm, respectively. The phytochemical analysis result showed that four extracts of stem of T. macrocarpa Jack. preliminary contained alkaloid, flavonoid, saponin and tanin compounds. It was concluded that ethylacetate and ethanol extracts of stem of T. macrocarpa Jack. possess a powerful anticancer and antioxidation activities.